Mechanisms of Nucleophilic Aromatic and Hetero-aromatic Substitution. Recent Developments - Claude F. Bernasconi (CHIMIA)
There are now at least five well defined mechanisms of nucleophilic aromatic and heteroaromatic substitution. Three of them, the SNAr, the benzyne and the SN1 mechanism, have been known for a long time, whereas the SRN1and the SN (ANRORC) mechanisms are relatively recent discoveries. The former is a radical chain mechanism which has a wide applicability in synthesis while the latter has only been found in heterocyclic systems and involves a nucleophilic addition followed by ring opening and ring closure processes. An SNAr mechanism, initiated by the transfer of an electron from the nucleophile to the substrate, has also been proposed, but evidence for it has not yet been conclusive. In recent years considerable progress has also been made in understanding the more subtle aspects of the older mechanisms. For example, base catalysis; in SNAr reactions with amine nucleophiles has been shown to be a consequence of rate limiting proton transfer despite the fact that proton transfer is diffusion controlled. Benzyne has been isolated and many theoretical calculations on its structure have been performed. The SN1 mechanism has been shown to involve reversible loss of nitrogen from arenediazonium ions, a fact of considerable import because it is the first example of a reaction of an organic species with nitrogen.